MANAGEMENT ACCOUNTABILITY OF PKU MUHAMMADIYAH SUKOHARJO HOSPITAL - Rahmawati Setyo Wigati; Djoko Suhardjanto (Media Riset Akuntansi, Auditing & Informasi, 2022)
The purpose of this study is to explain the accountability of PKU Muhammadiyah Sukoharjo hospital management. The method used is a qualitative method with a phenomenological perspective. Data collection techniques using interviews, observation and documentation. The results of this study indicate that there are five aspects in the management of hospital accountability, namely the first legal and honesty aspects, the second program aspects, the third process aspects, the fourth policy aspects, and the fifth is the financial aspect. The results of the study reveal that there is no transparency / accountability to the community related to the financial statements of PKU Muhammadiyah Sukoharjo Hospital. Hospital financial reports. PKU Muhammadiyah was not published due to the existence of a hospital financial reporting policy mechanism. However, in terms of the program PKU Hospital has improved with many trainings and workshops provided with the aim of providing quality and competent resources.